Research ethics and the challenge of whole-genome sequencing - McGuire, Amy L.; Caulfield, Timothy; Cho, Mildred K. (Nature reviews. Genetics, 2008)
As personal genome research advances, investigators and international research bodies must ensure ethical research conduct. The authors discuss three major ethical implications of personal genomics that relate to the participants, their next-of-kin and the data. The recent completion of the first two individual whole-genome sequences is a research milestone. As personal genome research advances, investigators and international research bodies must ensure ethical research conduct. We identify three major ethical considerations that have been implicated in whole-genome research: the return of research results to participants; the obligations, if any, that are owed to participants' relatives; and the future use of samples and data taken for whole-genome sequencing. Although the issues are not new, we discuss their implications for personal genomics and provide recommendations for appropriate management in the context of research involving individual whole-genome sequencing.